THE INFLUENCE OF EMOTIONAL QUOTIENT (EQ), HEDONIC SHOPING MOTIVATION, DISCOUNTS AND PEER CONFORMITY ON IMPULSE BUYING (CASE STUDY OF MAN 1 KEDIRI STUDENTS) - Amanah, Roudhotul; Sugiono, Sugiono; Subagyo, Subagyo (Nusantara Economics and Entrepreneurships Journals, 2025)
This research is motivated by the results of observations and experiences of researchers, that the marketplace offers many types of daily needs and also many digital products that make users more comfortable using the marketplace for their daily needs. These various offers make it easier for consumers to shop, causing unplanned purchases (impulse buying). Based on observations at Madrasah Aliyah Negeri (MAN) 1 Kediri, many students are interested in shopping without any prior planning. While the majority of their income is obtained from parents and they do not have their own income. So the authors are interested in conducting this research with the aim of knowing how the influence of emotional quentient, hedonic shoping motivation, discounts and peer conformity on impulse buying in the marketplace. This research uses a quantitative approach. The sampling method used purposive sampling with a sample size of 117 students. The data were analyzed through validity, reliability, classical assumptions and multiple linear regression tests with the help of SPSS for windows version 23. The results of the study simultaneously indicate that the variables of emotional quentient, hedonic shopper motivation, discounts and peer conformity have a significant influence on impulse buying. While partially the emotional quentient variable has a negative effect on impulse buying and the hedonic shoping motivaton variable, discounts and peer conformity have a positive and significant effect on impulse buying